Anaerobic utilization of Fe(III)‐xenosiderophores among Bacteroides species and the distinct assimilation of Fe(III)‐ferrichrome by Bacteroides fragilis within the genus. Issue 4 (11th April 2017) - Rocha, Edson R.; Krykunivsky, Anna S.
Abstract: In this study, we show that Bacteroides species utilize Fe(III)‐xenosiderophores as the only source of exogenous iron to support growth under iron‐limiting conditions in vitro anaerobically. Bacteroides fragilis was the only species able to utilize Fe(III)‐ferrichrome while Bacteroides vulgatus ATCC 8482 and Bacteroides thetaiotaomicron VPI 5482 were able to utilize both Fe(III)‐enterobactin and Fe(III)‐salmochelin S4 as the only source of iron in a dose‐dependent manner. We have investigated the way B. fragilis assimilates Fe(III)‐ferrichrome as initial model to understand the utilization of xenosiderophores in anaerobes. B. fragilis contains two outer membrane TonB‐dependent transporters (TBDTs), FchA1 and FchA2, which are homologues to Escherichia coli ferrichrome transporter FhuA. The disruption of fchA1 gene had only partial growth defect on Fe(III)‐ferrichrome while the fchA2 mutant had no growth defect compared to the parent strain. The genetic complementation of fchA1 gene restored growth to parent strain levels indicating that it plays a role in Fe(III)‐ferrichrome assimilation though we cannot rule out some functional overlap in transport systems as B. fragilis contains abundant TBDTs whose functions are yet not understood. However, the growth of B. fragilis on Fe(III)‐ferrichrome was abolished in a feoAB mutant indicating that Fe(III)‐ferrichrome transported into the periplasmic space was reduced in the periplasm releasing ferrous iron prior to transport through the FeoAB transport system. Moreover, the release of iron from the ferrichrome may be linked to the thiol redox system as the trxB deletion mutant was also unable to grow in the presence of Fe(III)‐ferrichrome. The genetic complementation of feoAB and trxB mutants completely restored growth on Fe(III)‐ferrichrome. Taken together, these findings show that Bacteroides species have developed mechanisms to utilize ferric iron bound to xenosiderophores under anaerobic growth conditions though the regulation and role in the biology of Bacteroides in the anaerobic intestinal environment remain to be understood. Abstract : Utilization of iron‐bound xenosiderophores by Bacteroides.